The uses of Comparative Law in criminal reform. Reflections on the Draft of the Criminal Code prepared by the Commission designated by Decree 103/2017 (2019)
This article aims to analyze one of the functions of Comparative Law. More specifically, its main purpose is to investigate how Comparative Law can be an auxiliary element to carry out the formulation of the legislative policy of a State. In this case fro